2017
DOI: 10.1098/rsob.170133
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of CXCL13 and heparan sulfate binding show that GAG binding site and cellular signalling rely on distinct domains

Abstract: Chemokines promote directional cell migration through binding to G-protein-coupled receptors, and as such are involved in a large array of developmental, homeostatic and pathological processes. They also interact with heparan sulfate (HS), the functional consequences of which depend on the respective location of the receptor- and the HS-binding sites, a detail that remains elusive for most chemokines. Here, to set up a biochemical framework to investigate how HS can regulate CXCL13 activity, we solved the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…the residues after the C-terminal -helix) of CXCL13 is incredibly dynamic, with multiple trajectories away from the core domain. Comparisons of two other published structures of human CXCL13 bound to single-chain variable fragment (scFv) molecules (Tu et al, 2016) as well as two solution structures of murine CXCL13 (Monneau et al, 2017) confirmed our finding of the rigidity of the core domain as well as the mobilities of the N-and C-termini. Collectively, our results provide the scientific community with a case study as to how some chemokine receptors can tolerate minor length and side-chain variation in the N-termini of their ligands and retain activity, as well as providing two unique structures of human CXCL13.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…the residues after the C-terminal -helix) of CXCL13 is incredibly dynamic, with multiple trajectories away from the core domain. Comparisons of two other published structures of human CXCL13 bound to single-chain variable fragment (scFv) molecules (Tu et al, 2016) as well as two solution structures of murine CXCL13 (Monneau et al, 2017) confirmed our finding of the rigidity of the core domain as well as the mobilities of the N-and C-termini. Collectively, our results provide the scientific community with a case study as to how some chemokine receptors can tolerate minor length and side-chain variation in the N-termini of their ligands and retain activity, as well as providing two unique structures of human CXCL13.…”
Section: Introductionsupporting
confidence: 84%
“…other time: in the solution structure of murine CXCL13 (Monneau et al, 2017). Further inspection of Met CXCL13 indicated that there is one monomer per asymmetric unit that forms a crystallographic dimer with a symmetry mate.…”
Section: Crystal Structure Of Met Cxcl13mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the role of CXCL13 as tissue-specific chemoattractant confined to lymph nodes and TLS, implicates the necessity for mechanisms restricting its diffusion and spatial distribution. The mechanisms for its tissue-specific local containment has recently been shown to rely on special molecular binding sites on CXCL13 for heparan sulfate side chains of proteoglycans on cells and within extracellular matrices [36]. These interactions are of utmost importance for chemokine gradients and haptotactic guidance of lymphocytes within tissues [37].…”
Section: Discussionmentioning
confidence: 99%
“…Our current studies and previous studies of hNACs show that residues from the N-loop and 40s loop also determine binding, that their contributions can be quite significant, and that the binding geometries can be quite diverse (24, 26 -29). Recent NMR studies of GAG binding of chemokines CXCL10, CXCL12, and CXCL13 also show diverse binding interfaces and geometries (41)(42)(43)(44). Considering all chemokines bind GAGs, it is very likely that each chemokine shows distinct GAG interactions.…”
Section: Discussionmentioning
confidence: 99%